A Guide for the Idealist Launching and Navigating Your Planning Career - Willson, Richard (Taylor & Francis, 2018)
A Guide for the Idealist is a must for young professionals seeking to put their idealism to work. Speaking to urban and regional planners and those in related fields, the book provides tools for the reader to make good choices, practice effectively, and find meaning in planning work. Built around concepts of idealism and realism, the book takes on the gap between the expectations and the constraints of practice. How to make an impact? How to decide when to compromise and when to fight for a core value? The book advises on career "launching" issues: doubt, decision-making, assessing types of work and work settings, and career planning. Then it explains principled adaptability as professional style. Subsequent chapters address early-practice issues: being right, avoiding wrong, navigating managers, organizations and teams, working with mentors, and understanding the career journey. Underpinning these dimensions is a call for planners to reflect on what they are doing as they are doing it. The advice provided is based on the experience of a planning professor who has also practiced planning throughout his career. The book includes personal anecdotes from the author and other planners about how they launched and managed their careers, and discussion/reflection questions for the reader to consider.